2009
DOI: 10.3390/md7020097
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Antimicrobial Epiphytic and Endophytic Fungi from Marine Organisms: Isolation, Bioassay and Taxonomy

Abstract: In the search for new marine derived antibiotics, 43 epi- and endophytic fungal strains were isolated from the surface or the inner tissue of different marine plants and invertebrates. Through preliminary and secondary screening, 10 of them were found to be able to produce broad-spectrum antimicrobial metabolites. By morphological and molecular biological methods, three active strains were characterized to be Penicillium glabrum, Fusarium oxysporum, and Alternaria alternata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 39 publications
0
59
2
2
Order By: Relevance
“…At the first stage, the screening was conducted by disc diffusion method of Kirby Bourer (4,8) This stage contains the preparation of aseptic equipment and materials, the selection of the colony, the preparation of the inoculum suspension, suspension standardized inoculum, cultivation on agar plates, the addition of antimicrobial discs, incubation, inhibition zone measurement and analysis of results. Results from this stage were the size of the inhibition zone that is formed, and will further be explained in the descriptive classification level of sensitivity according to Davis and Stout in Zhang (4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the first stage, the screening was conducted by disc diffusion method of Kirby Bourer (4,8) This stage contains the preparation of aseptic equipment and materials, the selection of the colony, the preparation of the inoculum suspension, suspension standardized inoculum, cultivation on agar plates, the addition of antimicrobial discs, incubation, inhibition zone measurement and analysis of results. Results from this stage were the size of the inhibition zone that is formed, and will further be explained in the descriptive classification level of sensitivity according to Davis and Stout in Zhang (4).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have found that the endophytic fungi are one of the main sources of producing new antibiotics [4]. Endophytic fungi isolated from a medicinal plant can produce secondary metabolites with the same number of lots of the host plant or even in a relatively higher amount.…”
Section: Introductionmentioning
confidence: 99%
“…The eight symbiotic fungal strains, both epiphytes and endophytes, were isolated from the marine flora and fauna samples using the method previously reported [6]. The samples were collected from the intertidal zone of Fujiazhuang beach (121°36′13.82″E, 38°48′36.66″N) in Dalian City, China, in October of 2008 and May of 2009.…”
Section: Bioactive Strains Under Investigationmentioning
confidence: 99%
“…24 Endophytic fungi were cultured in PDA for seven days at room temperature. Test bacteria were inoculated in Petri dishes with Mueller-Hinton Agar (MHA).…”
Section: Agar Plug Diffusion Assaymentioning
confidence: 99%